ANALISIS KEMAMPUAN PENALARAN MATEMATIK DALAM MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA SISWA SMP KELAS VIII DITINJAU DARI PERBEDAAN GENDER - Siti Nurjanah; Gida Kadarisma; Wahyu Setiawan (Departement of Mathematics Education, 2019)
The purpose of this study was to describe the mathematical reasoning abilities of students and examine errors in solving system problems of two variable linear equations in class VIII by categorizing students with low, medium and high mathematical reasoning abilities. The research method used is a qualitative descriptive method with a form of test research. The population taken is all private junior high school students in Bandung Regency with a sample of selected VIII-A class students in 30 students of Sulaiman Air Force Middle School. The test instrument provided is in the form of 5 questions. The results showed that reasoning ability in the material system of linear equations was two variables, namely for male students mathematical reasoning ability only reached 57% and in female students mathematical reasoning ability reached 63% of 30 students, so that students' mathematical reasoning ability in class VIII- A Suludan Air Base Space Middle School is male students have lower mathematical reasoning ability compared to female students